Low dose or low dose rate ionizing radiation-induced health effect in the human. (December 2018) - Tang, Feng Ru; Loganovsky, Konstantin
Abstract: The extensive literature review on human epidemiological studies suggests that low dose ionizing radiation (LDIR) (≤100 mSv) or low dose rate ionizing radiation (LDRIR) (<6mSv/H) exposure could induce either negative or positive health effects. These changes may depend on genetic background, age (prenatal day for embryo), sex, nature of radiation exposure, i.e., acute or chronic irradiation, radiation sources (such as atomic bomb attack, fallout from nuclear weapon test, nuclear power plant accidents, 60 Co-contaminated building, space radiation, high background radiation, medical examinations or procedures) and radionuclide components and human epidemiological experimental designs. Epidemiological and clinical studies show that LDIR or LDRIR exposure may induce cancer, congenital abnormalities, cardiovascular and cerebrovascular diseases, cognitive and other neuropsychiatric disorders, cataracts and other eye and somatic pathology (endocrine, bronchopulmonary, digestive, etc). LDIR or LDRIR exposure may also reduce mutation and cancer mortality rates. So far, the mechanisms of LDIR- or LDRIR -induced health effect are poorly understood. Further extensive studies are still needed to clarify under what circumstances, LDIR or LDRIR exposure may induce positive or negative effects, which may facilitate development of new therapeutic approaches to prevent or treat the radiation-induced human diseases or enhance radiation-induced positive health effect. Highlights: LDIR or LDRIR exposure induces health effects depend on genetic background, age (prenatal day for embryo), sex, nature of radiation exposure. Epidemiological and clinical studies show that LDIR or LDRIR exposure may induce cancer, congenital abnormalities, vascular diseases, cognitive impairment andcataracts. LDIR or LDRIR exposure may also reduce mutation and cancer mortality rates.